Glycaemic regulation, appetite and ex vivo oxidative stress in young adults following consumption of high-carbohydrate cereal bars fortified with polyphenol-rich berries. Issue 9 (7th May 2019) - Smith, Tracey J.; Karl, James Philip; Wilson, Marques A.; Whitney, Claire C.; Barrett, Ann; Farhadi, Nicole Favreau; Chen, Chung-Yen Oliver; Montain, Scott J.
Abstract: Consumption of certain berries appears to slow postprandial glucose absorption, attributable to polyphenols, which may benefit exercise and cognition, reduce appetite and/or oxidative stress. This randomised, crossover, placebo-controlled study determined whether polyphenol-rich fruits added to carbohydrate-based foods produce a dose-dependent moderation of postprandial glycaemic, glucoregulatory hormone, appetite and ex vivo oxidative stress responses. Twenty participants (eighteen males/two females; 24 (sd 5) years; BMI: 27 (sd 3) kg/m 2 ) consumed one of five cereal bars (approximately 88 % carbohydrate) containing no fruit ingredients (reference), freeze-dried black raspberries (10 or 20 % total weight; LOW-Rasp and HIGH-Rasp, respectively) and cranberry extract (0·5 or 1 % total weight; LOW-Cran and HIGH-Cran), on trials separated by ≥5 d. Postprandial peak/nadir from baseline (Δmax ) and incremental postprandial AUC over 60 and 180 min for glucose and other biochemistries were measured to examine the dose-dependent effects. Glucose AUC0–180 min trended towards being higher (43 %) after HIGH-Rasp v. LOW-Rasp ( P =0·06), with no glucose differences between the raspberry and reference bars. Relative to reference, HIGH-Rasp resulted in a 17 % lower Δmax insulin, 3 % lower C-peptide (AUC0–60 min and 3 % lower glucose-dependent insulinotropic polypeptide (AUC0–180 min ) P <0·05. No treatment effects were observed for the cranberry bars regarding glucose and glucoregulatory hormones, nor were there any treatment effects for either berry type regarding ex vivo oxidation, appetite-mediating hormones or appetite. Fortification with freeze-dried black raspberries (approximately 25 g, containing 1·2 g of polyphenols) seems to slightly improve the glucoregulatory hormone and glycaemic responses to a high-carbohydrate food item in young adults but did not affect appetite or oxidative stress responses at doses or with methods studied herein.